Motile Aeromonas Septicemia (MAS) Disease Resistance Test by Aeromonas hydrophila on Triploid Striped Catfish (Pangasianodon hypopthalmus) - Hartami, Prama; Ayuzar, Eva; Salamah , Salamah; Nurjannah, Lilis; Carman, Odang; Alimuddin , Alimuddin; Rafi, Muhammad; Fakhri, Muhammad (Journal of Aquaculture and Fish Health, 2024)
Motile Aeromonas Septicemia (MAS) disease caused by Aeromonas hydrophila is a common pathogen that attacks freshwater fish commodities, including triploid as the new strain of striped catfish. This study aimed to test the resistance of triploid striped catfish to MAS infection before being released to farmers as a new commodity to increase national striped catfish production. The test was carried out for two months at the Sukamandi Fish Breeding Research Institute, Subang by injecting A. hydrophila into triploid and diploid striped catfish. The challenge test was carried out by injecting the cultured A. hydrophila with a density of 107 cfu.mL-1 as much as 0.1 mL.ind-1 at fish intramuscularly in all treatments, while in the Control (-) treatment, 0.1 mL of PBS solution was injected.tail-1. The test striped catfish used for each treatment were 10 individuals measuring 9.23 – 9.65 cm, and weighing 7.1 – 9.23 g. Survival parameter data and blood description were analyzed quantitatively using Microsoft Excel 2010 and SPSS version 16.0 software with analysis of variance (ANOVA) at a 95% confidence interval. The results of re-characterization with biochemical tests showed that A. hydrophila were gram-negative, oxidase and catalase positive, motile, could fermentatively convert sugar, and could grow in blood media. The survival of triploid striped catfish after the test was 95%, total erythrocytes on day 7, and total leukocytes on the first day were significantly different from diploid striped catfish. Thus, it can be concluded that striped triploid striped catfish are more resistant to infection with A. hydrophila than diploid.